Review on the value of graduated elastic compression stockings after deep vein thrombosis - Kakkos, Stavros K.; Daskalopoulou, Stella S.; Daskalopoulos, Marios E.; Nicolaides, Andrew N.; Geroulakos, George (Thrombosis and Haemostasis, 2006)
Graduated elastic compression stockings (GECS) are commonly used in the primary prevention of deep vein thrombosis (DVT); however, their role in preventing recurrent DVT and also post-thrombotic syndrome is less well established. The aim of this review was to investigate the effect of GECS after DVT. A literature search was performed by two independent searchers in order to identify randomised controlled trials on the effect of GECS in preventing recurrent DVT and post-thrombotic syndrome. Four randomised trials, including 537 patients, were identified. Two of the studies demonstrated that below-knee GECS significantly reduced post-thrombotic syndrome during follow-up, while a smaller study showed equivocal results. GECS reduced the incidence of post-thrombotic syndrome from 54% to 25.2% [relative risk (RR) 0.47, 95% confidence interval (CI) 0.36-0.61] with the number needed to treat (NNT) being 4 (95% CI 2.7-5.0).The rate of recurrent asymptomatic DVT was also significantly reduced by GECS (RR 0.20, 95% CI 0.06-0.64; NNT 5); the reduction in symptomatic DVT was not significant (RR 0.79, 95% CI 0.50-1.26; NNT 34). In conclusion, there is level Ia evidence to suggest that GECS can significantly reduce the incidence of post-thrombotic syndrome (PTS) after DVT, and therefore these should be routinely prescribed. The evidence for recurrent DVT is less conclusive. Further research is needed towards standardising PTS diagnostic criteria and evaluating more effective preventive measures after DVT.
Keywords: Graduated elastic compression stockings; recurrent deep vein thrombosis; venous thromboembolism; post-thrombotic syndrome; prevention